2011
DOI: 10.1530/eje-11-0307
|View full text |Cite
|
Sign up to set email alerts
|

Negative illness perceptions are associated with impaired quality of life in patients after long-term remission of Cushing's syndrome

Abstract: Objective: Illness perceptions pertain to the pattern of beliefs patients develop about their illness. Illness perceptions are determinants of quality of life (QoL). Factors contributing to persisting impaired QoL after Cushing's syndrome (CS) remain largely unknown. Therefore, the objective of this study was to explore illness perceptions, as potentially modifiable psychological factors, in relation to QoL in patients with long-term remission of CS. Design: Cross-sectional study. Methods: We included patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 26 publications
5
55
3
1
Order By: Relevance
“…Similar results were found in recent studies using CushingQoL, with a mean score of 39G17 for active patients and 52G18 for cured patients (17,18). Nevertheless, up to two-thirds of cured patients still have limitations in the dimensions evaluated by the EuroQoL-5D profile, especially for pain/discomfort, which tends to be higher in surgically cured patients (65%) than in active disease (56%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were found in recent studies using CushingQoL, with a mean score of 39G17 for active patients and 52G18 for cured patients (17,18). Nevertheless, up to two-thirds of cured patients still have limitations in the dimensions evaluated by the EuroQoL-5D profile, especially for pain/discomfort, which tends to be higher in surgically cured patients (65%) than in active disease (56%).…”
Section: Discussionsupporting
confidence: 87%
“…Patients who were adrenal insufficient after surgery and required hydrocortisone did not differ in the CushingQoL score and EuroQoL-VAS compared with those who were eucortisolemic. Previous studies have reported no effects of hydrocortisone substitution on QoL in CS (3,18) but also that adrenal insufficiency in general, as well as Addison's disease and hypopituitarism, are related to worse HRQoL (4,20). No effect of cortisol-lowering drugs, like metyrapone and ketoconazole, was observed when comparing patients who were treated or not with these drugs, even though the groups were small.…”
Section: Discussionmentioning
confidence: 81%
“…This may explain the chronic cognitive impairments described in patients in long-term remission of CS (4,34), which may negatively influence QOL. Other explanations for the impaired QOL could be the previous experience of suffering a severe illness, ineffective coping strategies or illness perceptions (35,36). Future research will have to determine the exact causes of impaired QOL in patients in long-term remission of CS.…”
Section: Discussionmentioning
confidence: 99%
“…The physical symptoms of acromegaly include frontal bossing, swelling of extremities, and swelling of soft tissue (i.e., heart, intestines, and tongue) (2) resulting from chronic GH overexposure. Psychological issues include negative illness perceptions (3) and a decreased quality of life (QoL) patients can be treated with suppressive medication, such as somatostatin analogs (1) and/or GH receptor agonists (5). Upon remission of acromegaly, physical and psychological symptoms usually improve, although QoL often does not return to premorbid levels (6,7).…”
Section: Introductionmentioning
confidence: 99%